ACUTE POISONING WITH METHYL ALCOHOL: A CLINICAL STUDY IN GEZIRA STATE, SUDAN - Ali Salim, Abdel Rahman; Mohamadani, A.A. (Gezira Journal of Health Sciences, 2006)
14 patients were admitted in March 2005 to Wad Medani Teaching Hospital in Wad Medani, the capital of Gezira State, Sudan, with features of an acute poisoning which are described in this paper. The history taken, directly from the patients or their relatives, revealed that all of them drank a substance known among them as spirit . They consumed it as an alternative to a locally-made alcoholic beverage known as Aragi This substance was obtained from small shops which utilize it for manufacturing locally-made perfumes. These small shops are widely distributed in different towns in Sudan. This substance proved to be methanol on analysis in the Forensic and Criminology Laboratory of the Ministry of Interior (personal communication).As this substance has less obvious smell compared to that of ethanol, people who consume it could mingle with others with no easy detection of alcohol consumption. They even called it the Social drink for the above reason while having the same mood-elating effect.All of the patients developed blindness. Thirteen of them eventually died within 30 hours from consumption of the substance; only one survived but remained blind.